Discussion of Why Do EPS Forecast Error and Dispersion Not Vary with Scale? Implications for Analyst and Managerial Behavior - BALL, RYAN T. (Journal of Accounting Research, 2011)
Cheong and Thomas (2011) provide a new perspective on the behavior of the distribution of EPS forecast error magnitudes as a function of share price. Specifically, they explore several economic-based explanations, related to analyst and manager behavior, in order to understand why measures of EPS forecast error variation do not appear to vary with share price. In this discussion, I explore two additional issues, unrelated to the behavior of managers and analysts, which may significantly contribute to the observed lack of scale variation in EPS forecast error magnitudes in the United States: (1) EPS data in I/B/E/S are reported to the nearest penny, which may render detection of scale variation extremely difficult in a sample of U.S. firms, and (2) there are differences between the measurement of EPS forecast error variation in Cheong and Thomas relative to prior literature. I provided evidence that both issues confound the interpretation of the lack of scale variation observed in U.S. firms and have strong implications for future research exploring EPS forecast error magnitudes.